Text- und Data-Mining in den digitalen Geisteswissenschaften Gutachten zu den urheberrechtlichen Rahmenbedingungen im Rahmen des Forschungsprojektes "XSample - Text- und Data-Mining auf geschützten Werken durch Auszüge transparent erschließen" - Kleinkopf, Felicitas Lea (Ubiquity Press, 2023)
The legal opinion was developed in the context of the ""XSample"" project funded by the Ministry of Science, Research and the Arts of the State of Baden-Württemberg. The aim of the project was to examine the copyright possibilities in research with text and data mining. The content of this expert opinion is the legal assessment of the copyright relevance of real use cases from the field of digital humanities as well as the analysis of the permission of the individual work steps. A central subject of this research process is the safeguarding of the requirements of good research practice, which is accompanied by the question of whether the corpora created for text and data mining may be passed on for research purposes, at least in part. In this way, a certain legal certainty is to be achieved for researchers who are confronted with questions about the scope of the new text and data mining permissions in the Copyright Act - §§ 44b, 60d - in order to make research on copyrighted works reproducible in the future to an extent sufficient for research.